EXPLORING THE INTERPLAY BETWEEN COMMUNICATION COMPLEXITY AND NETWORK DENSITY IN PDNS - Sharma, Pinki; Begum, Reshma; Katare, Rakesh Kumar; Waoo, Akhilesh A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research investigates the features of a PDN interconnection network for Parallel and Distributed architecture. PDN is a novel and evolving architecture for parallel and distributed systems. It is an extremely effective method of joining a group of nodes into a network with a diameter equal to 2. At a distance of one or two nodes are joined together. A Perfect Difference Set is a mathematical technique for estimating the improved number of nodes in an extremal manner for a perfect difference network. We represented the Adjacency Matrix of PDN in geometric form and separated it into four pieces i.e., represented the geometric relationship among PDN processors. We next estimated the Network Density and Communication Complexity of PDN and its subparts and presented a quick comparison of them.